1993
DOI: 10.1177/026309239301200103
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Airborne Sound from 50-20,000 Hz into the Abdomen of Sheep

Abstract: The transmission of audible sounds from the environment of the pregnant woman to the foetus is of growing interest to obstetricians who utilize foetal vibracoustic stimulation in their examinations, and to occupational health professionals who believe that high-intensity sound in the workplace is potentially damaging to the foetus. Earlier reports on transmission of sound into the abdomen and uterus of sheep revealed a significant amount of sound attenuation at frequencies above 2,000 Hz. and some enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Concerning airborne stimuli -emitted via an aircoupled or distant source -human and sheep studies have demonstrated that their transmission depends on: (a) the frequency composition of the signal, and (b) the in utero location of the acoustic transducer (Peters, Abrams, Gerhardt, & Griffiths, 1993a). Frequencies below around 400 Hz suffer almost no pressure attenuation and may even be enhanced, relative to the external level (Peters, Gerhardt, Abrams, & Longmate, 1993b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning airborne stimuli -emitted via an aircoupled or distant source -human and sheep studies have demonstrated that their transmission depends on: (a) the frequency composition of the signal, and (b) the in utero location of the acoustic transducer (Peters, Abrams, Gerhardt, & Griffiths, 1993a). Frequencies below around 400 Hz suffer almost no pressure attenuation and may even be enhanced, relative to the external level (Peters, Gerhardt, Abrams, & Longmate, 1993b).…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed by Vince and colleagues (1982;Vince et al, 1985), Gerhardt, Abrams, and Oliver (1990), and Richards et al (1992) suggested that in utero sound transmission is likely to occur according to a nonlinear pattern. More precisely, a recent study analyzing transmission of airborne sounds from 50 -20,000 Hz conducted by Peters et al (1993a) in sheep demonstrated, among other frequency-related effects, that: "...from 12,500 to 20,000 Hz there was a reversal of the attenuation pattern showing that the effectiveness of transmission gradually improved again..." (p. 22). Concerning the location of the transducer, isosonic curves defined by Peters et al (1993b) in sheep demonstrated that the in utero pressure level of an airborne source decreased when the distance to the source of the hydrophone placed in the cavity was increased.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of sound into the fetal environment in humans [Bench, 1968;Querleu et al, 1988] and sheep [Armitage et al, 1980;Peters et al, 1993] has been well documented. The fluids and tissues surrounding the fetus act as a low-pass filter.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Bench reported 19 dB of attenuation at 0.2 kHz and up to 78 dB at 8.0 kHz. Peters et al [1993] examined the transmission of externally generated white noise at different levels from air into the uterus of a nonpregnant ewe. Negative attenuation, at 0.05, 0.063, 0.4, 1.0, and 1.25 kHz was noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation